2021
DOI: 10.1177/0031512521990330
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Movement Skill Proficiency Among British Primary School Children: Analysis at a Behavioral Component Level

Abstract: Fundamental Movement Skill (FMS) proficiency is an important antecedent of physical activity for children and adolescents. Many studies report children’s overall FMS proficiency to be low. However, in order to develop effective intervention strategies, it is critical to understand FMS proficiency at a behavioral component level. This study investigated British primary school children’s FMS proficiency across all three FMS domains, reporting proficiency at both an individual skill level and at a behavioral comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 64 publications
(126 reference statements)
1
39
1
1
Order By: Relevance
“…Nonetheless, social norms have led to skills not being developed by girls and boys in the early years, due to the underrepresentation of the skill within a sex’s stereotypical play opportunities [ 45 , 46 ]. Therefore, appealing to both sexes and reducing sex discrepancies in achievement of both FMSs development and PA levels, where sex differences consistently appear [ 9 , 47 ] must be addressed. Establishing interventions that allow developmentally appropriate activities for all may be a crucial step in the EYFS.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, social norms have led to skills not being developed by girls and boys in the early years, due to the underrepresentation of the skill within a sex’s stereotypical play opportunities [ 45 , 46 ]. Therefore, appealing to both sexes and reducing sex discrepancies in achievement of both FMSs development and PA levels, where sex differences consistently appear [ 9 , 47 ] must be addressed. Establishing interventions that allow developmentally appropriate activities for all may be a crucial step in the EYFS.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Duncan et al's study highlighted that children attending schools in England, aged 6-7 years, are typically only at an elementary stage of motor skill development (i.e., where performance of skills is judged to be incorrect on two or more behavioral components of a skill). Furthermore, Lawson et al (2021), in English 7-to 10-year-olds, and using the TGMD-2, reported that that no children, aged 7-10 years of age, achieved mastery in all skills assessed and over a quarter (27%) did not achieve mastery in any of the skills within the TGMD-2. Eyre et al (2018) similarly identified overall "poor" FMS performance (via the TGMD-2) in English 5-year-olds and significantly poorer locomotor skill in English children from South Asian backgrounds, compared to their White and Black counterparts.…”
Section: United Kingdom-specific MC Levelsmentioning
confidence: 99%
“…Fundamental motor skills (FMS) are organized series of basic movements patterns that involve various body parts to perform a specific act, i.e., they are movements necessary for goal-directed activity ( Logan et al, 2018 ; Lawson et al, 2021 ). They include three types of skills ( Goodway et al, 2019 ; Bolger et al, 2020 ): locomotor skills (different movements to transport the body from one location to another such as running or sliding); manipulative or object-control skills (movements to impart force to an object or receive force from an object such as throwing or catching); and stability or balance skills [they are necessary to maintain controlled positions during both static (still) activities, e.g., standing on one leg, and dynamic (moving) activities, such as climbing].…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental motor skills are the foundation or base for future more complex motor skills. In other words, they are the initial building blocks to acquire the more complex specialized skills required in play, games, recreational activities, physical activities and sports for children, adolescents and adults ( Hulteen et al, 2018 ; Logan et al, 2018 ; Morley et al, 2019 ; Gu et al, 2021 ; Lawson et al, 2021 ). Consequently, failure to develop competency in FMS will make difficult to learn more advanced/specialized forms of these skills ( Getchell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%